2022
DOI: 10.1371/journal.pone.0273705
|View full text |Cite
|
Sign up to set email alerts
|

Comparative whole transcriptome analysis of gene expression in three canine soft tissue sarcoma types

Abstract: Soft tissue sarcomas are pleiotropic tumors of mesenchymal cell origin. These tumors are rare in humans but common in veterinary practice, where they comprise up to 15% of canine skin and subcutaneous cancers. Because they present similar morphologies, primary sites, and growth characteristics, they are treated similarly, generally by surgical resection followed by radiation therapy. Previous studies have examined a variety of genetic changes as potential drivers of tumorigenesis and progression in soft tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 88 publications
(104 reference statements)
4
3
0
Order By: Relevance
“…This could be due to variability in analyses techniques and/or histological characterization of canine PNSTs. Similar to our study, a recent RNAseq study of canine STS subtypes, also showed elevated expression of GLI and CLECB1 in PNST samples (48)…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This could be due to variability in analyses techniques and/or histological characterization of canine PNSTs. Similar to our study, a recent RNAseq study of canine STS subtypes, also showed elevated expression of GLI and CLECB1 in PNST samples (48)…”
Section: Discussionsupporting
confidence: 92%
“…This could be due to variability in analyses techniques and/or histological characterization of canine PNSTs. Similar to our study, a recent RNAseq study of canine STS subtypes, also showed elevated expression of GLI and CLECB1 in PNST samples (48), but failed to confirm elevation of S100 and vimentin in PNST samples. Further studies at both transcript and protein levels are required to determine specific molecular markers for PNST.…”
Section: Discussionsupporting
confidence: 75%
“…However, responses remained short lived, ranging from 7 to 90 days. This is similar to previous findings evaluating HSA and STS responses to other chemotherapy agents 18,19,22,38–41,51 ; where despite sharing a mesenchymal origin, these tumours demonstrate diverging genomic landscapes and clinical behaviours 53,54 . The gene expression profiles and mutations of HSA and STS may impact differences in chemosensitivity 53–57 .…”
Section: Discussionsupporting
confidence: 87%
“…This is similar to previous findings evaluating HSA and STS responses to other chemotherapy agents 18,19,22,[38][39][40][41]51 ; where despite sharing a mesenchymal origin, these tumours demonstrate diverging genomic landscapes and clinical behaviours. 53,54 The gene expression profiles and mutations of HSA and STS may impact differences in chemosensitivity. [53][54][55][56][57] Furthermore, HSA display rapid progression resulting from high mitotic activity, 58,59 making them potentially susceptible to cytotoxic chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation